A first sample of faint radio sources with virtually complete redshifts: I. Infrared images, the Hubble diagram, and the alignment effect - Eales, S; Rawlings, S; Law-Green, D; Cotter, G; Lacy, M (1997)
We have obtained redshifts and infrared images for a sample of faint B2/6C radio sources whose fluxes are about six times fainter than those of sources in the bright 3C sample. We now have unambiguous redshifts for 90% of the sources, making this the first faint radio sample with such complete redshift information. We find that the infrared Hubble diagrams (K versus z) of the 3C sample and the B2/6C sample are similar at a low redshift (z < 0.6), but by a redshift about 1 the 6C/B2 galaxies are on average about 0.6 mags fainter in the K-band than 3C galaxies at the same redshift. This suggests that the bright K-magnitudes of 3C galaxies at a redshift of about 1 are not the result of stellar evolution, but of a correlation between infrared and radio luminosity. We also find that the infrared stuctures of B2/6C galaxies at z=1 are less clearly aligned with their radio structures than 3C galaxies at this redshift, implying that the strength of the alignment effect depends on radio luminosity. Finally, above a redshift of 2 we find that the dispersion in the K-z relation of the B2/6C sample is about 2.7 times greater than that at low redshift, a result which is expected if at these redshifts we are beginning to penetrate into the epoch in which radio galaxies formed.